The incidence, treatment strategies and outcomes of acute coronary syndromes in the "reperfusion network" of different hospital types in the Czech Republic: results of the Czech evaluation of acute coronary syndromes in hospitalized patients (CZECH) registry - Widimsky, Petr; Zelizko, Michal; Jansky, Petr; Tousek, Frantisek; Holm, Frantisek; Aschermann, Michael; CZECH investigators (International journal of cardiology, 2007)
AIMS: To analyze the incidence, treatment strategies and outcomes of acute coronary syndromes (ACS) in Czech population. METHODS AND RESULTS: ACS diagnosis was confirmed in 1345 of 1921 (70%) consecutively admitted patients with suspected ACS. ACS incidence was 3248 cases/million/year and the annual incidence of confirmed myocardial infarction was 1960 per million. In-hospital mortality was 5.1% (10.0% with Q-MI, 4.4% with non-Q-MI, and 0.9% with UAP). Coronary angiography was performed in 92% of STEMI (followed by primary PCI in 83%, by CABG in 3%, by conservative therapy in 6%). Thrombolysis was used in only 1% of patients. Reperfusion therapy was thus used in 87% of all STEMI patients. Discharge medication included aspirin in 95%, a statin in 76%, a beta-blocker in 78%, an ACE inhibitor in 50%, clopidogrel in 60%, and ticlopidine in 4% of patients. CONCLUSIONS: In-hospital mortality of ACS in the Czech network of PCI and non-PCI hospitals is low. Nationwide application of primary PCI strategy for STEMI is feasible and increases the overall use of reperfusion therapy.
Keywords: inhibitory agregace trombocytů; trombolytická terapie; výsledek terapie; Adrenergic beta-Antagonists; koronární bypass; Male; mortalita v nemocnicích; Česká republika; Hydroxymethylglutaryl-CoA Reductase Inhibitors; inhibitory ACE; Coronary Artery Bypass; statiny; Adult; nestabilní angina pectoris; Aged; dospělí; beta blokátory; mužské pohlaví; senioři; incidence; registrace; Angiotensin-Converting Enzyme Inhibitors; Coronary Angiography; infarkt myokardu; Thrombolytic Therapy; Hospital Mortality; Czech Republic; Treatment Outcome; senioři nad 80 let; lidé; ženské pohlaví; Angina, Unstable; Humans; Myocardial Infarction; Aged, 80 and over; koronární angiografie; Registries; Female; lidé středního věku; Incidence; Platelet Aggregation Inhibitors; Middle Aged